Interactions between Dispatchers and Truck Drivers in a High Turnover Context - Fournier, Pierre-Sébastien; Lamontagne, Sophie; Gagnon, Julie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
The North American trucking industry has been facing chronic issues related to the retention of a skilled workforce since the end of the 1980s. These issues have both direct economic and social impact; for example, high driver turnover has been linked to higher accident rates. Research has revealed a clear link between the dispatcher’s role and driver turnover, yet little is known about the interactions of this relationship in day-to-day work experience. The aim of the present article, therefore, is to document the dynamic environment shaping interactions between dispatchers and truck drivers in addressing issues related to high turnover. In order to capture the daily interactions of these players, a qualitative approach was used, based on 17 individual interviews and three group discussions with dispatchers, truck drivers and labour and management representatives from 11 different Quebec-based organizations. The results reveal four key characteristics influencing the day-to-day dynamics of trucking operations: 1) the importance of dispatcher-driver interaction in efficient and quality work operations; 2) the precedence of customer satisfaction in these interactions; 3) the interdependent nature of the dispatcher-driver relationship; and lastly, 4) the role of listening and mutual respect. More specifically, the results suggest that dispatcher-driver interactions tend to occur in a high-pressure environment where work demands often necessitate prioritizing operational concerns over interpersonal ones. They also demonstrate that a bi-directional, “win-win” relationship based on constructive interactions, listening and mutual respect are essential conditions in achieving both work efficiency and job satisfaction. These results appear to confirm the findings of several previous studies and shed new light on understanding the relationship between these players.